2018
DOI: 10.5194/tc-2018-84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling the fate of surface melt on the Larsen C Ice Shelf

Abstract: Abstract. Surface melt lakes lower the albedo of ice shelves leading to additional surface melting. This can substantially alter the surface energy balance and internal temperature and density profiles of the ice shelf. Evidence suggests that melt lakes also played a pivotal role in the sudden collapse of the Larsen B Ice Shelf in 2002.Here a recently developed, high physical fidelity model accounting for the development cycle of melt lakes is applied to the Larsen C Ice Shelf, Antarctica's most northern ice s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The disappearance of hundreds of lakes in Cabinet Inlet on Larsen C over 10 days in 2003 and three weeks in 2007 is also suggestive of hydrofracture drainage (Luckman et al, 2014), as observed on Larsen B (Scambos et al, 2003(Scambos et al, , 2009. The possibility of meltwater-driven hydrofracture on Larsen C has been highlighted by 1D ice shelf model simulations of future lake distributions (Buzzard et al, 2018b). In particular, larger lakes that migrate towards the front of the Larsen C Ice Shelf under warmer atmospheric conditions may deepen sufficiently to remain unfrozen between melt seasons, thereby pre-disposing them for hydrofracture (Buzzard et al, 2018b).…”
Section: Antarctic Peninsulamentioning
confidence: 74%
See 2 more Smart Citations
“…The disappearance of hundreds of lakes in Cabinet Inlet on Larsen C over 10 days in 2003 and three weeks in 2007 is also suggestive of hydrofracture drainage (Luckman et al, 2014), as observed on Larsen B (Scambos et al, 2003(Scambos et al, , 2009. The possibility of meltwater-driven hydrofracture on Larsen C has been highlighted by 1D ice shelf model simulations of future lake distributions (Buzzard et al, 2018b). In particular, larger lakes that migrate towards the front of the Larsen C Ice Shelf under warmer atmospheric conditions may deepen sufficiently to remain unfrozen between melt seasons, thereby pre-disposing them for hydrofracture (Buzzard et al, 2018b).…”
Section: Antarctic Peninsulamentioning
confidence: 74%
“…The possibility of meltwater-driven hydrofracture on Larsen C has been highlighted by 1D ice shelf model simulations of future lake distributions (Buzzard et al, 2018b). In particular, larger lakes that migrate towards the front of the Larsen C Ice Shelf under warmer atmospheric conditions may deepen sufficiently to remain unfrozen between melt seasons, thereby pre-disposing them for hydrofracture (Buzzard et al, 2018b). The depleted firn air thickness of Larsen C (0.3m in western inlets) also increases the likelihood of extensive SGL ponding and future instability, driven by sustained föhn-enhanced melting (Alley et al, 2018;Holland et al, 2011).…”
Section: Antarctic Peninsulamentioning
confidence: 99%
See 1 more Smart Citation
“…This depth was chosen as during initial testing this was the minimum size of domain where temperature and density changes were not found to reach the bottom of the model domain. The model resolution of 5 cm grid spacing was chosen as it was found that results for resolutions of 5 cm and below were identical and therefore 5 cm was chosen as the resolution for the model in order to minimize the time taken for the model to run (Buzzard, ). The vertical domain is allowed to change to account for surface melting and snowfall.…”
Section: Numerical Implementation Of the Modelmentioning
confidence: 99%
“…The code was initially tested using prescribed forcing and the model was found to conserve mass with an accuracy of 99.7% and conserve energy during the solution of the heat equation with an accuracy greater than 99.9% (Buzzard, ).…”
Section: Numerical Implementation Of the Modelmentioning
confidence: 99%